2021
DOI: 10.1111/ppc.12742
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between nursing students' digital and smartphone addiction levels and nomophobia: A descriptive, correlational study

Abstract: Purpose This study aimed to investigate the relationship between nursing students' digital addiction and smartphone addiction levels and nomophobia. Methods This is a descriptive, correlational study. It was conducted with 215 nursing students in a university located in northeastern Turkey. Results A positive and moderate correlation was found between students' nomophobia levels with smartphone addiction and digital addiction levels (p < 0.05). Analysis of the regression coefficients determined that smartphone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Similar studies also found a relationship between depression, and anxiety, and smartphone addiction [28,29]. Excessive use of digital devices and mobile phones decreases students' academic success and satisfaction with life disrupts their sleep quality, negatively affects them and isolates their social life and verbal communication [8,30]. In the study, it was found that the level of smartphone addiction was statistically significantly higher in the students with poor/very poor sleep time and quality.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Similar studies also found a relationship between depression, and anxiety, and smartphone addiction [28,29]. Excessive use of digital devices and mobile phones decreases students' academic success and satisfaction with life disrupts their sleep quality, negatively affects them and isolates their social life and verbal communication [8,30]. In the study, it was found that the level of smartphone addiction was statistically significantly higher in the students with poor/very poor sleep time and quality.…”
Section: Discussionmentioning
confidence: 71%
“…In studies on smartphones, the use of smartphones is stated to be common among young people, and this situation is associated with addictive behavior. It is reported that when smartphones are used excessively, they can negatively affect learning in the classroom and interpersonal communication, and cause security problems [5][6][7][8]. The adolescent, who tries to socialize with a smartphone and reduce the problems s/he experiences, actually becomes more individualized and disconnects from real life [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have reported negative psychological effects such as smartphone addiction, stress, uneasiness, and causing memory impairment with excessive smartphone use (Faiola et al, 2018; O'Connell, 2020). Another problem exacerbated by smartphones is nomophobia (Anshari et al, 2019; Çobanoğlu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A condition associated with smartphone addiction is nomophobia. A number of studies have found a strong association between nomophobia, smartphone addiction, and digital addiction (Çobanoğlu et al, 2021 ). Nomophobia, which stands for “NoMobilePhone” phobia, refers to an individual’s fear of not having contact with their mobile phone (Gurbuz & Ozkan, 2020 ; King et al, 2010 ; Yildirim & Correia, 2015 ).…”
mentioning
confidence: 99%